Association between complete vaccination and anemia in children under 5 years of age, in Peru, in the years 2019 to 2021 - Cabada-Yépez, Helena (2023)
The present study consists of observing the relationship between immunizations and anemia in children under 5 years of age. Anemia is a public health problem worldwide and Latin America is no exception. Particularly, for the Peruvian case, approximately one third of children under 5 years of age present this disease. The consequences vary depending on the degree of anemia that occurs; Mild anemia being the most common case among minors. In order to combat anemia, the Peruvian Ministry of Health proposes various actions, including vaccination against rotavirus and pneumococcus as some of them. From this perspective, the question arises if there is a relationship between immunization and anemia. For this, taking information from the Demographic Survey of Family Health (ENDES), estimates are made regarding the possession and level of anemia in children under 5 years of age, taking as the main variable that children are up to date with their vaccinations, according to their age in months. Vaccination is based on Ministerial Resolution No. 719-2018/MINSA and the study period is from 2019 to 2021, considering the year in which the pandemic began. It can be seen that in 2019, the magnitude of complete immunization, both individually and collectively, is greater than in subsequent years. From this premise the main conclusion can be drawn, which indicates that there is an inverse association between complete immunization and the tenure of anemia in children under 5 years of age.